F: Pengalaman Transisi Perawat Baru Mengikuti Program Preceptorship di Training Center RS X - Fitriyani Dwi Sulistyowati; Fulgensius Surianto; Indriati Kusumaningsih (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
ABSTRACTThe transition of newly graduated nurses into professional practice is a complex phase and is highly vulnerable to transition shock, particularly in type C hospitals with high work demands. A preceptorship program was developed to support newly graduated nurses in adapting to the work environment; however, their experiences during and after participation in the program still need to be explored in depth. This study aimed to explore the experiences of newly graduated nurses during and after participating in the preceptorship program at the Training Center of Hospital X. This study employed a qualitative approach with a descriptive phenomenological design. Participants were selected purposively using the principle of maximum variation sampling and involved 18 participants, consisting of 10 newly graduated nurses as the main participants, 3 preceptors, and 5 head nurses as triangulation informants. Data were collected through semi-structured in-depth interviews conducted both offline and online, and were analyzed using Colaizzi’s seven-step method with the support of NVivo 15. Data credibility was strengthened through source triangulation and member checking. The findings generated five major themes: newly graduated nurses’ feelings during the preceptorship program, the support they received during the transition process, the barriers they encountered, the adaptive strategies or responses they employed, and the nature of transition after completing the preceptorship program. Overall, the transition occurred gradually, beginning with initial enthusiasm, followed by anxiety and pressure, and eventually developing into courage, self-confidence, and readiness to perform the professional role. The preceptorship program served as an important bridge in supporting clinical readiness, emotional adaptation, and the formation of professional identity among newly graduated nurses.Keywords: newly graduated nurses; preceptorship; professional transition; descriptive phenomenology; type C hospital